ISOLATION AND ANTIMICROBIAL ACTIVITY TESTING OF METABOLITE COMPOUNDS FROM THE ENDOPHYTIC FUNGI CLADOPHIALOPHORA NYINGCHIENSIS S51 - Lusianawati, Ratih
Antimicrobial resistance in pathogens has been declared by the WHO as one of the top ten greatest public health threats to humanity. New treatments for antimicrobial therapy can be sought from abundant natural resources in Indonesia, such as endophytic fungi. This research aimed to test the antimicrobial activity of extracts, fractions, and isolate of metabolite compounds from the endophytic fungi Cladophialophora nyingchiensis S51 against Escherichia coli, Staphylococcus aureus, and Candida albicans. The research stages began with fungal media extraction using liquid-liquid extraction and fungal biomass extraction using maceration. The extract showing better antimicrobial activity, which is the media extract, was fractionated using vacuum liquid chromatography, and then the dominant compound was isolated using radial chromatography. Extracts, fractions, and isolate of dominant compound were tested for antimicrobial activity using the disc diffusion method, and Minimum Inhibitory Concentration and Minimum Bactericidal Concentration were determined using microdilution and drop test methods. From the fractionation results, four combined fractions were obtained to test their antimicrobial activity, and it was found that each fraction provided inhibition zones against E. coli of 8.07, 10.04, 10.65, and 7.90 mm, respectively; against S. aureus of 12.45, 10.95, 10.25, and 0 mm, respectively; and against C. albicans of 9.32, 8.80, 8.22, and 8.55 mm, respectively. Subsequently, isolation and purification of dominant compound were conducted, and the identification of compound classes in the isolates was performed by spraying several spray reagents, revealing that the isolated compound is a phenolic compound. The isolate showed antimicrobial activity against E. coli and S. aureus but not against C. albicans. MIC and MBC against E. coli are 2048 ?g/mL, and the MIC and MBC against S. aureus were found to be 1024 ?g/mL and 2048 ?g/mL.